Chinese investors investment strategies in the Australian residential property market. (2nd September 2017) - Wong, Peng Yew; Higgins, David M.; Wakefield, Ron
Abstract: Active participation by foreign investors in Australian residential property market is common subsequent to the Global Financial Crisis 2008. Many residential properties in the Australian capital cities were purchased by overseas buyers. An estimated 18% of new dwellings in Sydney and 14% in Melbourne were purchased by foreigners in 2014. Simultaneously, house prices rose by 6.0% in 2014 and 5.0% in 2015 in the Australian capital cities. The focus of this research is to uncover the emerging determinants for the Australian residential property market. Cross border semi-structured interviews were conducted in Shanghai (China), the first such undertaken in Australia. Some unique investment strategies of the private investors from China emphasised on non-capitalist factors, such as early education and residential tourism, were identified along with some insights on the Chinese government policies that have incentivised the cross border investments from China. It is believed that understanding these investment strategies will assist policy makers to effectively manage the overheated Australian residential property market without compromising the steady flow of Foreign Real Estate Investment.